THE INFLUENCE OF INFLATION, TRADE, AND FARMERS' EXCHANGE RATE ON ECONOMIC GROWTH IN LAMPUNG PROVINCE - Muhamad Irpan Nurhab (Jurnal Saintifik, 2022)
This study aims to see how much influence inflation, trade, and farmer exchange rates have on economic growth in Lampung Province. The method used is a descriptive-analytical method with a quantitative approach with multiple regression analysis tests. The data used is secondary data from the Central Statistics Agency (BPS) from 2018-2021. The results of the study showed that simultaneously there was no significant influence between inflation, trade, and farmer exchange rates on economic growth. The three indicators of economic growth that have a significant effect are inflation, the higher the inflation, the lower the economic growth, while the lower the inflation, the more positive the economic growth will be. Partial testing, inflation does not have a positive effect on economic growth, but hurts economic growth, meaning that decreasing inflation will have a positive impact on economic growth and conversely increasing inflation will not have a positive effect on economic growth. . Trade does not have a positive impact on economic growth, meaning that increasing trade will not have a positive effect on economic growth. The Farmer's Exchange Rate does not have a positive effect on Economic Growth, meaning that the greater the Farmer's Exchange Rate, it will not have a positive effect on Economic Growth.